NILAI PENDIDIKAN KARAKTER DALAM NOVEL MENGURAI RINDU KARYA NANG SYAMSUDDIN - Aprimadedi Aprimadedi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
minimize these cases, it is necessary to replant the values ​​of character education from an early age. The values ​​of character education in the novel can be used as learning materials at schools. After the author read the novel Mengurai Rindu by Nang Syamsuddin, the author found many character education values. Type of research was a qualitative research using the content analysis method and the literary approach used in this study is the mimetic approach, and the data for this research were the speech, actions of the characters, and the narrator's exposure that contains the values ​​of character education in the novel Mengurai Rindu by Nang Syamsuddin. The data is then identified and classified based on the theory used and each data collected based on indications of character education values ​​is discussed one by one. The results of this study show that; (1) there are 34 data containing honest character education values, (2) there are 12 data containing intelligent character education values, (3) there are 47 data containing caring character education values, and (4) there are 12 data containing the values ​​of strong character education. Based on the results of the study, it can be concluded that the values ​​of character education that are most often found in the novel Mengurai Rindu by Nang Syamsuddin are values ​​of caring character education, while the least found are values ​​of intelligent and tough character education.